2016
DOI: 10.1016/j.jcma.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

High daily doses of trimethoprim/sulfamethoxazole are an independent risk factor for adverse reactions in patients with pneumocystis pneumonia and AIDS

Abstract: We found a high incidence of ADRs among patients with PJP and AIDS treated with TMP/SMX, and most involved the skin and liver. A daily dose of ≥ 16 mg/kg of TMP/SMX and age 34 years were independent risk factors for ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
16
1
1
Order By: Relevance
“…36,37 Chang et al reported that high daily doses of CTX were an independent risk factor for cutaneous and other adverse drug reactions. 38 We did not measure the serum concentrations of CTX, so it is possible that plasma and tissue concentrations of CTX might have influenced the adverse outcomes in our study. However, a previous case-control study by Pirmohamed et al failed to demonstrate an association between genetic polymorphisms in drug metabolizing enzymes with CTX hypersensitivity in patients with HIV.…”
Section: Articlementioning
confidence: 96%
See 1 more Smart Citation
“…36,37 Chang et al reported that high daily doses of CTX were an independent risk factor for cutaneous and other adverse drug reactions. 38 We did not measure the serum concentrations of CTX, so it is possible that plasma and tissue concentrations of CTX might have influenced the adverse outcomes in our study. However, a previous case-control study by Pirmohamed et al failed to demonstrate an association between genetic polymorphisms in drug metabolizing enzymes with CTX hypersensitivity in patients with HIV.…”
Section: Articlementioning
confidence: 96%
“…A recent case-control study in the Thai population reported an association between CTX-induced SJS/TEN and HLA-B*15:02 (odds ratio (OR) = 3.91; 95% confidence interval (CI): 1.42-10.92; P = 0.0037), HLA-C*06:02 (OR = 11.84; 95% CI: 1.24-566.04; P = 0.0131) and HLA-C*08:01 (OR = 3.53; 95% CI: 1.21-10.40; P = 0.0108). 12 In European patients, the presence of HLA-B* 38 was significantly associated with sulfamethoxazole-related SJS/ TEN, but the different allelic variants of HLA-B*38 did not show significant association with sulfamethoxazole-related SJS/TEN. 13 Additionally, a strong association between SJS/TEN and trimethoprim alone was observed.…”
Section: Genetic Association Of Co-trimoxazole-induced Severe Cutaneomentioning
confidence: 98%
“…According to current guidelines for the prevention and treatment of opportunistic infections in HIV-infected patients, the preferred treatment for PCP is oral or intravenous trimethoprim-sulfamethoxazole (TMP-SMX; TMP, 15 to 20 mg/kg/day; SMX, 75 to 100 mg/kg/day) for 21 days (6). However, clinicians often have to reduce the dose or switch to an alternative treatment due to the occurrence of adverse events (7).…”
mentioning
confidence: 99%
“…; Chang et al. ; Hernandez et al. ) The risk of sulfonamide HS increases with HIV disease progression, with higher risk seen at lower CD4 + counts.…”
Section: Introductionmentioning
confidence: 99%